Без четырех углов дом не строится — rosyjskie ludowe praktyki magiczne związane z gospodarstwem domowym - Rybarczyk-Dyjewska, Joanna (Przegląd Wschodnioeuropejski, 2018)
The aim of the present work is a presentation of Russian folk magical practices connected with the running of a home. The first part of the article reflects on the significance of the home (it symbolism) in Eastern Slavonic culture as well as belief in the magical powers of the spirits protecting the homestead. The second part of the article analyses pragmatically the spells from the group домоведческие и хозяйственные заговоры [domestic and household spells]. The characterised material shows that the verbal magical interaction was based first and foremost on the use of an arousal strategy, being the categorical significance of the imperative mood.